Collaboration among international organizations of physical education and sports. The point of view of the president and secretary general of the FIEP (Fiep Bulletin - online, 2015)
During the meetings held at the National Institute of Popular Education at Marty-le-Roi, France from 8th to 11th May 1967, being present leaders of the ICSPE, FIEP, FIMS and ICHPER in order to study to study forms of collaborations among International Organizations of Physical Education and Sport, the opinion of the FIEP has Been thus Expressed.